High temperature fatigue of heat treated secondary AlSi7Cu3Mg alloys. (September 2020) - De Mori, Alessandro; Timelli, Giulio; Berto, Filippo; Fabrizi, Alberto
Highlights: Peak hardness is reached after 4 h at 453 K due to complex Al-Si-Cu-Mg precipitates. Fatigue behaviour is minimally affected by testing temperature up to 473 K. Coarsening of the strengthening precipitates compromise fatigue behaviour at 573 K. The failure mode changes from mixed to ductile above 473 K testing temperature. Abstract: The high-temperature fatigue behaviour of a heat treated AlSi7Cu3Mg alloy is reported. Fatigue testing has been performed at room and higher temperatures (473 and 573 K) on specimens previously solubilised at 758 K for 24 h and further aged at 453 K for 8 h. Microstructural and fractographic investigations have been used to quantitatively examine the evolution of strengthening precipitates and the different fracture mechanisms. The results show how the fatigue behaviour is comparable in the temperature range between 293 and 473 K. Then, the fatigue strength decreases by increasing the testing temperature from 473 to 573 K. The uniform distribution of fine strengthening precipitates in the α-Al matrix is affected by higher test temperature, which promotes coarsening phenomena of the precipitates. The failure mode changes from brittle to ductile at 573 K.